Nuclear species of mixed bird flocks in Atlantic Forest in the Serra de Paranapiacaba, southeastern Brazil - Machado, Caio Graco (SITIENTIBUS série Ciências Biológicas, 2002)
This study investigated the structure of mixed bird flocks in an area of Atlantic Forest in the Serra de Paranapiacaba, São Paulo State, Brazil. Twelve monthly visits were carried out from April 1990 to March 1991, with 36 hours of fieldwork each. During the sightings of these mixed flocks, the following variables were recorded: species composition, species distribution inside the flock, height of the vegetation where the birds foraged, size of the flocks (number of individuals), and the behavior of the component species. Five bird species observed within the mixed flocks were assigned the role of nuclear species: Basileuterus culicivorus (Licht., 1830), Philydor rufus (Vieillot, 1818), Phylloscartes oustaleti (Sclater, 1887), Hylophilus poicilotis (Temminck, 1822), and Orthogonys chloricterus (Vieillot, 1819). None of these species, however, completely fit the parameters that define a nuclear species. On the other hand, mixed-flocks with two or more of these species were significantly larger than flocks with only one, or none, of these five species. Thus, the cohesive force for mixed flocks of birds in this area of Atlantic Forest does not seem to be exerted by one or two typical nuclear species, but rather by a group of species acting as formers and maintainers of mixed flocks.